Controversias y vulneracion de garantías y derechos originados por el despido ineficaz en mujeres en periodo de lactancia. - Apolo Montero, Keren Jemima (2017)
This Work of degree has as general objective the study of the case number 00487-2016 Demand of Indemnification for Untimely Dismissal; process that brought knowledge lawyer. Ana Paulina Yepez de los Reyes, Judge of the Judicial Unit of The Work with headquarters in the Canton Machala; analysis that was based on the constitutional rights and right of the pregnant Women; judgment that was carried out by means of the hermeneutic, deductive, inductive and comparative method using indirect observation technic; as investigation tools that helped to realizing the reflection of the Constitutional Ecuadorian